Comparison of Quality of Life in Transfemoral Amputee Using Bone‐Anchored Prostheses vs. Socket Prostheses: A Systemic Review and Meta‐Analysis - Janice Tan; Nafisa Zilani; Rezaul Karim; Bijendra Patel (Orthopaedic Surgery)
ABSTRACT Amputation has a profound impact on an individual's quality of life (QoL) and functional ability. While socket prostheses are the current first‐line treatment, they often cause socket‐related issues. Bone‐anchored prostheses (BAP) have been introduced to address these problems and improve the amputee experience. This systematic review and meta‐analysis aim to compare the QoL between bone‐anchored and socket prostheses in transfemoral amputees. A systematic review and meta‐analysis were conducted from November 2023 to July 2024, following PRISMA guidelines. Databases including PUBMED, EMBASE, Scopus, Cochrane, and Web of Science were searched. Studies of single‐arm trial design comparing pre‐ and post‐operative outcomes were selected based on specific inclusion and exclusion criteria. Statistical analysis was performed using inverse variance with a random effect model. The primary outcome was QoL, measured using the Questionnaire for Persons with a Transfemoral Amputation (Q‐TFA) and 36‐Item Short Form Survey (SF‐36), and the secondary outcome was mobility, assessed by the 6‐Minute Walk Test (6MWT). Subgroup analyses compared different types of BAP (Press‐fit vs. Screw‐type) on QoL. Thirteen NRCTs with 398 participants were included. Significant improvements in QoL were observed in all Q‐TFA domains and the SF‐36 Physical Component Score (PCS), but not in the SF‐36 Mental Component Score (MCS). Mobility improved significantly as measured by the six‐minute walk test (6MWT). No significant differences in QoL were found between Press‐fit and Screw‐type BAP implants. Overall, BAP significantly improve both QoL and mobility, but study limitations currently restrict their use to individuals with socket‐related complications. As such, it cannot yet be universally recommended as a first‐line intervention.